2015
DOI: 10.1111/epi.12944
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a role for cystatin B gene in juvenile myoclonic epilepsy

Abstract: Laura Mumoli is a postdoctoral fellow with special interest in epilepsy. SUMMARYGenetic factors play a major role in the etiology of juvenile myoclonic epilepsy (JME), a common form of idiopathic generalized epilepsy, but so far, genes related to JME remain largely unknown. JME shares electroclinical features with Unverricht-Lundborg disease (progressive myoclonic epilepsy type 1; EPM1), a form of progressive myoclonus epilepsy characterized by myoclonus, epilepsy, and gradual neurologic deterioration. EPM1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…They described a case of a compound heterozygous female patient affected by a mild phenotype that was mistaken for juvenile myoclonic epilepsy (genotype screening was performed for a distant family history of EPM1). It is worth noting that CSTB mutations were never found in juvenile myoclonic epilepsy . On these data we speculate that in heterozygous compound patients an association of genetic and gender‐specific factors can reduce the efficacy of residual Cystatin B (to counteract damages resulting from endogenous protease activity).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…They described a case of a compound heterozygous female patient affected by a mild phenotype that was mistaken for juvenile myoclonic epilepsy (genotype screening was performed for a distant family history of EPM1). It is worth noting that CSTB mutations were never found in juvenile myoclonic epilepsy . On these data we speculate that in heterozygous compound patients an association of genetic and gender‐specific factors can reduce the efficacy of residual Cystatin B (to counteract damages resulting from endogenous protease activity).…”
Section: Discussionmentioning
confidence: 80%
“…It is worth noting that CSTB mutations were never found in juvenile myoclonic epilepsy. 8 On these data we speculate that in heterozygous compound patients an association of genetic and gender-specific factors can reduce the efficacy of residual Cystatin B (to counteract damages resulting from endogenous protease activity). Even if a haploinsufficiency of CSTB seems to not affect heterozygous compound patients, 5 a functional deficit of mutated protein cannot be excluded.…”
Section: Discussionmentioning
confidence: 85%
“…This clinical presentation could be more frequent in Tunisia than in European countries since it was shown that the course of the disease is more severe in Northern Europe than in Maghreb (Gargouri-Berrechid et al, 2016). In addition, Laura Mumoli and colleagues showed an absence of mutation associated with ULD in 33 unrelated patients with JME from Italy (Mumoli et al, 2015). The size of repeats in Family 1 was within the classic range and even larger than that of Family 2, which does not account for the very mild phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although ULD remains uncommon, it has been increasingly diagnosed among patients with drug-resistant myoclonic epilepsy, as shown, for instance, in Holland (de Haan et al, 2004). However, whereas the most common mutation in ULD affects the cystatin B gene (CSTB), no evidence for a role of this gene was found in sporadic or familial cases of juvenile myoclonic epilepsy (JME) (Mumoli et al, 2015). The availability of molecular genetic diagnostic techniques in developed countries has certainly helped.…”
mentioning
confidence: 99%